Factors Related To The Nutritional Status Of Children In The Working Area Of Alasa Public Health Center, North Nias Regency 2019 - Piuskosmas Fau; Dedi MizwarTarihoran Tarihoran (Institute of Computer Science (IOCS), 2019)
Based on the 2015 MDG's target, the prevalence of malnutrition and under-five children is 15.5%, this prevalence rate is included in the high category. From the results of the monitoring report on the nutritional status of children under five at the Alasa Public Health Center, which is one of the health centers in North Nias, the cases of malnutrition and malnutrition in children under five are still high, with a prevalence of 9.93%. The purpose of this study was to determine the factors associated with the nutritional status of children under five. The population of mothers who have toddlers by means of sampling is done by simple random. The sample in this study was 15% of the total population as many as 65 people. Data were collected using the Chi-Square test.